Pelatihan dan Pembelajaran Tumbuhan Melalui Herbarium Kering di Kelas 5 SD Negeri Patung - Oksal, Efriyana; Wiriatmaja, Nuraini Ulya; Lawrence, Yoel; Zadrax, Adellino; Seda, Ananda Putri; Situmorang, Larissa Kristina T.T.; Sidauruk, Christina; Sianturi, Dody Jhonatan Wilfiez; Manalu, Mely Grace Manalu; Riansyah, Irza; Kibtiyah, Maryatul; Gloria, Meilina; Ayu, Yulia Agustina; Maulida, Maulida; Seprianto, Seprianto (Universitas Islam Indonesia, 2025)
This service aims to increase the understanding of grade 5 students at SD Negeri Patung about plant diversity through training and introduction to the herbarium. The problem faced is students' lack of knowledge about plant types and the importance of conservation. The methods used include the first stage of socialization of herbarium activities and the second stage of dry herbarium training. The results of the service show an increase in student's knowledge about plant classification, as well as skills in collecting and preserving plant specimens. As many as 80% of students showed high enthusiasm and were able to explain the process of making a herbarium well. In conclusion, this training not only increases students' knowledge about plants but also fosters a sense of love for the environment. The use of herbarium as a learning tool has proven effective in introducing the concept of biodiversity to the younger generation. It is hoped that this program can be implemented on an ongoing basis to support environmental education in elementary schools.